The Collected Lyric Poems of Luís de Camões - Camões, Luís de, 1524?-1580 (Book collections on Project MUSE., 2008)
Gives English readers the first comprehensive collection of Camoes sonnets, songs, elegies, hymms, odes, eclogues, and other poems-more than 280 lyrics altogether, all rendered in engaging verse. Camoes was the first great European artist to cross into the Southern Hemisphere, and his poetry bears the marks of nearly two decades spent in north and east Africa, the Persian Gulf, India, and Macau. From an elegy set in Morocco, to a hymn written at Cape Guardafui on the northern tip of Somalia, to the first modern European love poems for a non-European woman, these lyrics reflect Camoes's encounters with radically unfamiliar peoples and places.